2001
DOI: 10.1093/brain/124.2.378
|View full text |Cite
|
Sign up to set email alerts
|

Subthalamic nucleus, sensorimotor cortex and muscle interrelationships in Parkinson's disease

Abstract: Ten patients with Parkinson's disease were seen following bilateral or unilateral implantation of macroelectrodes into the subthalamic nucleus. Local field potentials (LFPs) were recorded from adjacent subthalamic nucleus macroelectrode (STNME) contacts simultaneously with EEG activity over the supplementary motor (Cz-FCz) and sensorimotor (C3/4-FC3/4) areas and EMG activity from the contralateral wrist extensors during isometric and phasic wrist movements. Significant coherence was seen between STNME LFPs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

25
169
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 253 publications
(196 citation statements)
references
References 36 publications
25
169
2
Order By: Relevance
“…The brain rhythms, such as beta, gamma, or alpha, recorded in these cortical areas are tightly related to the motor action and ability. The abnormities of the oscillatory activity in relevant frequency band have been shown to be associated with both the motor symptoms and the disease progression of PD (Marsden et al 2001;Rowland et al 2015). Then, the changes of PE or OI at C3 or C4 channels may be developed into a potential marker of the dyskinesia caused by PD.…”
Section: Discussionmentioning
confidence: 99%
“…The brain rhythms, such as beta, gamma, or alpha, recorded in these cortical areas are tightly related to the motor action and ability. The abnormities of the oscillatory activity in relevant frequency band have been shown to be associated with both the motor symptoms and the disease progression of PD (Marsden et al 2001;Rowland et al 2015). Then, the changes of PE or OI at C3 or C4 channels may be developed into a potential marker of the dyskinesia caused by PD.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in vivo recordings from the rat STN demonstrate a close correspondence between synchronized neuronal and LFP activity after cortical stimulation (Magill et al 2004). Phase estimates between the subthalamic area and cortical EEG suggest that cortical inputs drive STN LFP beta oscillatory activity (Fogelson et al 2006;Marsden et al 2001b;Williams et al 2002) by two possible routes, either indirectly by the striatum/globus pallidus externus (GPe) or by a direct projection to the subthalamic nucleus (Parent and Hazrati 1995). Moreover, previous studies in a rodent model of parkinsonism established that the cerebral cortex can induce pathological patterns of neuronal activity in the STN, perhaps as the result of greater sensitivity of the STN to rhythmic cortical inputs (Magill et al 2001;Paz et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…A dissociation between beta oscillatory LFPs and the clinical symptoms was also observed by Priori et al (2004), who showed that anticholinergic drug orphenadrine improved rigidity and tremor but also increased beta oscillatory activity. Dopaminergic medication and active movements are known to decrease STN beta synchronization (Brown et al 2001;Foffani et al 2005;Kuhn et al 2004;Levy et al 2002;Marsden et al 2001b;Priori et al 2002Priori et al , 2004 and deep brain stimulation in the STN may alleviate PD symptoms by disrupting this oscillatory activity (Brown et al 2004;Filali et al 2004;Jahanshahi et al 2000;Lozano et al 2002). It was previously hypothesized that dopamine action on the striatum acts as a filter for cortical input to the STN (Doyle et al 2005;Magill et al 2001Magill et al , 2004Sharott et al 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…basal ganglia | local field potentials | beta band | sequential movement | synchronization O scillations of brain activity in the beta band (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) Hz) have been implicated in sensorimotor control and integration (1)(2)(3)(4)(5) and are pathologically synchronized and exaggerated in Parkinson's disease (6)(7)(8)(9)(10)(11). Although reports have published examples of very brief (<150 ms) bursts of beta-band oscillation (12)(13)(14)(15), the analysis of beta-band activity has focused primarily on data averaged over trials, which show variations in average beta-band power occurring on a time scale of seconds.…”
mentioning
confidence: 99%